PERAN STAKEHOLDERS DALAM MEWUJUDKAN ZERO WASTE CITY DI - Amanda Natasya Putri; Kismartini Kismartini; R Slamet Santoso (Journal of Public Policy and Management Review, 2022)
The problem experienced by Depok City is the high generation of waste every year so it must be handled together. Realizing a zero waste city is carried out through handling and reducing waste. The purpose of this study is to identify stakeholders and the role of stakeholders in realizing Zero Waste City in Depok City. This research method is descriptive qualitative. The results of the study show that stakeholders classified as players, namely the Mayor of Depok has a role as a policy creator, Department of Environment and Cleanliness of Depok City has a role as a policy creator, coordinator, facilitator, implementor. Stakeholders classified as subjects are the Regional Development Planning Agency (Bappeda) of Depok City has a role as coordinator, Department of Public Works and Spatial Planning of Depok City has the role of a facilitator, the Main Waste Bank and Unit Waste Bank have the role of implementor and facilitator, the District Coordinator and Village Coordinator have the role of facilitator. Stakeholders classified as crowds are Districts, Village, and RT/RW each has a role as implementor and facilitators. The Indonesian Retail Entrepreneurs Association (Depok City Branch), Educational Institutions, and Pelapak each having a role as implementor. Suggestions that can be given are giving strict sanctions, providing training to socialitators, carrying out official cooperation, strengthening by each stakeholder, conducting and increasing supervision of waste banks, and forming unit waste as many as possible.